Efforts to Modify Dental Practices in Badung Regency in Facing the COVID-19 Pandemic - Desak Nyoman A. Susanti; Putri Rejeki; Alexander K. Wijaya (e-GiGi, 2022)
Abstract: Dentist has a high risk of being infected of COVID-19. This study aimed to determine the practice modification efforts carried out by dentists in Badung regency in facing the COVID-19 pandemic. This study used a mixed method design with a sequential explanatory strategy. Quantitative research was conducted with a questionnaire that was arranged based on PB PDGI guidelines and has been tested for validity and reliability with 72 respondents. Qualitative research was conducted by doing in-depth interview with two informants who had filled out the questionnaire to find out the reasons for the choice of answers and the possibility of other practice modifications carried out. The results showed that modifications to patient management procedures have been carried out such as screening the patients, asking patients to wash their hands, limiting the distance in the waiting room, and measuring body temperature. Modifications to the transmission prevention management carried out by dentists such as the use of complete PPE, limiting the duration of contact with patients, asking patients to rinse their mouth with povidone iodine, and installing exhaust fans in the practice room. The modifications that are slightly carried out are delaying the elective treatment and the use of rubber dams. In conclusion, dentists in Badung regency have made 83% modifications to patient management procedures and 93% modifications to the transmission prevention management recommended by PDGI, while the use of rubber dam is the least modification effort done because dentists are not used to it.Keywords: COVID-19; dentist; practice modificationÂ Â Abstrak: Dokter gigi merupakan profesi yang memiliki risiko tinggi tertular Coronavirus diseases (COVID-19). Penelitian ini bertujuan untuk mengetahui upaya modifikasi praktik yang dilakukan dokter gigi di Kabupaten Badung dalam menghadapi pandemi COVID-19. Desain penelitian ialah mixed method dengan strategi eksplanatoris sekuensial. Penelitian kuantitatif dilakukan menggunakan kuesioner yang disusun berdasarkan pedoman PB PDGI dan telah diuji validitas dan reliabilitasnya dengan 72 responden. Penelitian kualitatif dilakukan dengan wawancara mendalam kepada dua orang informan yang telah mengisi kuesioner untuk mengetahui alasan pilihan jawaban serta kemungkinan modifikasi praktik lainnya yang dilakukan. Hasil penelitian menunjukkan modifikasi prosedur tata kelola pasien yang telah dilakukan seperti melakukan skrining pasien, meminta pasien mencuci tangan, membatasi jarak di ruang tunggu, dan pengukuran suhu tubuh. Modifikasi tata laksana pencegahan transmisi yang dilakukan dokter gigi seperti penggunaan APD lengkap, membatasi durasi kontak dengan pasien, meminta pasien berkumur dengan povidone iodine, serta pemasangan exhaust fan di ruang praktik. Modifikasi yang masih sedikit dilakukan yaitu penundaan perawatan yang bersifat elektif serta penggunaan rubber dam. Simpulan penelitian ini ialah dokter gigi di Kabupaten Badung telah melakukan 83% modifikasi prosedur tata kelola pasien dan 93% modifikasi tata laksana pencegahan transmisi yang direkomendasikan oleh PDGI, sedangkan penggunaan rubber dam merupakan upaya modifikasi yang paling sedikit dilakukan (33%) dikarenakan dokter gigi belum terbiasa.Kata kunci: COVID-19; dokter gigi; modifikasi praktik